2017
DOI: 10.1093/heapol/czx074
|View full text |Cite
|
Sign up to set email alerts
|

Migrant tuberculosis patient needs and health system response along the Thailand–Myanmar border

Abstract: This article aims to identify how the health system in Tak province, Thailand has responded to migrants’ barriers to tuberculosis (TB) treatment. Our qualitatively driven multi-methods project utilized focus group discussions, key informant interviews, and a survey of community health volunteers to collect data in 2014 from multiple perspectives. Migrants identified legal status and transportation difficulties as the primary barriers to seeking TB treatment. Lack of financial resources and difficulties locatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Furthermore, the linkage between HICS and public health security could be observed as an accelerator to the likelihood of the HICS selling. The concern over spreading certain infectious diseases from migrants to the wider Thai public (such as tuberculosis, HIV, syphilis and malaria) was a major factor which encouraged providers to sell the HICS [ 35 , 36 , 37 , 38 , 39 , 40 ]. As a result, the relationship in access to the HICS and public health security was positive as shown in R2 in the CLD.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the linkage between HICS and public health security could be observed as an accelerator to the likelihood of the HICS selling. The concern over spreading certain infectious diseases from migrants to the wider Thai public (such as tuberculosis, HIV, syphilis and malaria) was a major factor which encouraged providers to sell the HICS [ 35 , 36 , 37 , 38 , 39 , 40 ]. As a result, the relationship in access to the HICS and public health security was positive as shown in R2 in the CLD.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the linkage between HICS and public health security can be observed as an accelerator to the likelihood of the HICS selling. The concern over spreading certain infectious diseases from migrants to the wider Thai public (such as tuberculosis, HIV, syphilis and malaria) that could cause public health threats is a major factor which encourages providers to sell the HICS [30][31][32][33][34][35]. As a result, the relationship in access to the HICS and public health security is positive as shown in R2 in the CLD.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the study of Tchirhart, et al [36] which reported that insurance, and access to free or low-cost services were major factors affecting access to health care system among migrant TB patients. Moreover, migrant TB patients are in serious need of health system response along the Thailand-Myanmar border [37]. Therefore, migrant workers particularly those who are living in Thailand illegally are insecure regarding access to health care system.…”
Section: Discussionmentioning
confidence: 99%